Fiduciary Guarantee in Banking Transactions: Positive Law and Sharia Law Perspective - Reni Anggriani; Aisyah Ajeng Putri Riyanto; Cyabriena Asela (Universitas Sriwijaya, 2023)
The process of transferring rights from the debtor to the creditor is solely based on trust. Fiduciary guarantees are a public need to apply guarantee law as a defense. on the implementation of consumer financing agreement agreements. Consumer agreements that are not accompanied by additional agreements result in the imposition of guarantees using general guarantees, so that the rights from material guarantees do not apply to him. This article aims to analyze the position and implementation of fiduciary guarantees in banking transactions from the perspective of positive and sharia law. The article uses normative legal research methods using statutory approaches and qualitative approaches. Article 1132 of the Civil Code finds that fiduciary guarantees in a positive legal perspective empower creditors to ask for compensation from the debtor by taking ownership of the promised guarantee and can be implemented directly without waiting for a court decision. While in the perspective of sharia law the term fiduciary guarantee is not recognized, in practice Islamic banks adopt the concept of fiduciary guarantee by using the term